Effect of the excitation waveform on the average power and peak power delivered by a piezoelectric generator. (1st November 2019) - Nadaud, Kevin; Poulin-Vittrant, Guylaine; Alquier, Daniel
Graphical abstract: Highlights: Harmonic content of the mechanical excitation influences the optimal load. Optimal load range to maximize mean power is broadened for waveforms containing numerous harmonics. Peak power is largely higher than mean power for waveforms with rich harmonic content. Abstract: The theoretical power delivered by piezoelectric generators (PG) is a key parameter for their design optimization and for the determination of the power management circuit which should be designed especially for the targeted device to be supplied. Most often, when the PG is connected to a resistive load, a maximum of average power occurs at a given load value which should be determined by sweeping the resistive load. Although the determination of this optimal load is obvious in the case of a sine signal, as it is matching the internal impedance of the PG, the cases of non-sine signals are more complex. In this paper, we show that the waveform of the mechanical force applied to the PG significantly influences the generated power and the optimal load. We propose a method to predict the average power produced by a PG as a function of the load, even if the waveform is not a sine. The study is focused on a square waveform with variable exponential rising time, corresponding to realistic mechanical excitations, and shows that the force rising time drastically influences the mean power delivered by PGs having a capacitive internal impedance, for example some ZnO nanowires-based PGs. We also show that the peak instantaneous power, often reported as PG performance metric in literature, largely overestimates the truly available power.